Subconjunto terminológico da classificação internacional para a prática de enfermagem - CIPE® para a pessoa com tuberculose - Silva, Ludimila Paiva Zamprogno (2019)
Introduction: Tuberculosis is a public health problem. Early identification and timely treatment should be a priority target for health professionals to reduce the real and potential problems of people affected by the disease, contributing to a favorable outcome. Nursing care for people with tuberculosis is organized by applying the nursing process, and the elements of its practice are represented by means of a terminology. The nursing process, supported by a nursing theory and recorded by a standardized terminology, may reflect on the quality of care provided to people with tuberculosis. Objective: To develop a subset ICNP® terminology for the care of people with tuberculosis guided by Wanda Aguiar Horta's Theory of Basic Human Needs. Methodology: This is a methodological study, which was developed in five stages: 1st) identification and validation of relevant terms for the person with tuberculosis based on the literature; 2nd) cross-mapping of the terms identified in the first step, using ICNP® terms; 3rd) construction of diagnostic statements, results and nursing interventions; 4th) validation of the diagnostic statements and results of nursing interventions by nurses who assist the person with tuberculosis in the city of Serra; 5th) establishment of a subset of the ICNP® terminology guided by the theoretical model of basic human needs of Wanda Horta for the person with tuberculosis. Results: A ICNP® terminology subset for the care of people with tuberculosis, containing 51 diagnoses and outcomes and 264 nursing interventions was developed and validated by primary health care nurses and structured according to Wanda Horta's theory of basic human needs. Product: An assistive piece of technology called ICNP® terminology subset for people with tuberculosis to be implanted in primary health care in the city of Serra, Espirito Santo. Conclusion: The developed subset is a culture-modifying technological instrument in which the biggest beneficiary is the person with tuberculosis. Through this instrument it is possible to identify the needs of the person with tuberculosis, to assist nurses in their clinical practice, to disseminate the ICNP® terminology to nurses in Serra, and the perspective of adding the ICNP® terminology subset to the person with tuberculosis to the electronic medical record, for use by nurses of primary health care.